STUDI TINGKAT PENGETAHUAN MASYARAKAT TENTANG GANGGUAN JIWA DI DESA BANJAR KEMANTREN BUDURAN SIDOARJO - Sya?diyah, Hidayatus (Universitas Nahdlatul Ulama Surabaya, 2016)
the study of public knowledge level about mental illness in the village of Banjar Kemantren Buduran Sidoarjo. Mental disorders are a deviation from the ideal state of a mental health. An understanding of the condition of mental illness characterized myths often makes the family often treat people with mental disorders unfairly. Problems with mental disorders has long been ignored, therefore the purpose of this study was to determine the level of public knowledge about mental disorders in the village of Banjar Kemantren Buduran Sidoarjo. This research used descriptive design with cross sectional method, a population of 300 families living in the village of Banjar Kemantren Buduran Sidoarjo, sampling technique used was Non-Probability Sampling method purposive sampling approach, the sample consisted of 171 families living in the village of Banjar Kemantren Buduran Sidoarjo. The variable in this study was the level of public knowledge about mental disorders in the village of Banjar Kemantren Buduran Sidoarjo. Data were collected by questionnaires and were analised with descriptive design. The results showed the level of public knowledge in the village of Banjar Kemantren Buduran Sidoarjo about mental illness was pretty average. Looking at the data above that need to improve the quality of human resources both from their families and from the health workers in an effort to increase public knowledge about mental disorders.